PENGARUH PERUBAHAN JUMLAH SUDU TURBIN TURGO TERHADAP DAYA OUTPUT PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) - Ida Bagus Made Pandwa Putra; I Wayan Arta Wijaya; I Gusti Ngurah Janardana (Jurnal SPEKTRUM, 2022)
The increase in demand for electrical energy in Indonesia causes a reduction in conventional fuel reserves. This situation forces people to look for alternative energy sources or commonly callednew and renewable energy (RE). Seeing the geographical condition of the environment in Indonesiawhich has the potential for the development of electrical energy by utilizing the flow of water, it iscalled a Micro Hydro Power Plant (PLTMH). In implementing MHP, one type of impulse turbine canbe used, namely the Turgo turbine. This study focused on knowing the effect of variations in thenumber of blades on a turgo turbine on rotational speed, torque, voltage, current and power producedby PLTMH using a Turgo turbine, with variations in the number of blades used, namely 18,16,14,9,8,and 7 blades. The method used in this research is quantitative experimental, all combinations ofparameters tested get the result that the highest output characteristic value occurs using a runnerwith a number of 18 blades, where the voltage, current, and output power are 8.30 Volts, 0, 88Ampere, and 7.27 Watt. The fastest turbine rotation results are 782.8 rpm before being connected toa generator and 565.4 rpm after being connected to a generator, while the generator rotation resultsare 1062.4 rpm. The highest torque produced is 0.1Nm, the maximum efficiency obtained at therunner blade variation is 18 blades, which is 1.1%.